Carcinosarcoma of the vulva: a rare case report - Barasha S. Bharadwaj; Upasana Kalita; Muktanjalee Deka; Jagannath D. Sarma; Adahra Patricia Beso; Asreen Suhana; B. C. Goswami (International Journal of Research in Medical Sciences, 2023)
Carcinosarcomas are rare and clinically aggressive neoplasms with poor outcome. A very few cases has been reported in the literature. We present a case of a 54 yrs woman with bleeding per vagina for 1.5 months. On per vaginal examination, a lump of size 3×2 cm was found over the left anterior region of vulva. CECT abdomen revealed a well-defined heterogeneously enhancing lesion with calcific foci involving both labia minora. MRI pelvis reveals carcinoma left vulva with involvement of lower 3rd of vaginal wall. Histopathological examination showed features suggestive of carcinosarcoma of the vulva. This was further confirmed by immunohistochemistry which showed positivity for CK, SMA, caldesmon and negative for S100, CD34, desmin, CD31, ERG and MyoD1. Because it is a very rare tumor with severe prognosis, we presented this case as this case report can be a useful addition to the literature.